Physical Properties Of Ultisol Soil In Pangkatan Sub-District With The Provision Of Organic Material Types - Syawal Harahap, Fitra; Harahap, Arman; Arman, Iman; Haholongan Sidabukke, Simon (International Journal of Science and Environment (IJSE), 2025)
This study entitled the provision of various organic materials on physical properties and ultisols in Pangkatan Sub-District Labuhan Batu Regency which was carried out in the experimental garden at the Labuhan Batu University campus, North Sumatra. This study aims to determine the best type of organic material to improve the physical properties of ultisol soil from the Rantau Selatan land at the Labuhan Batu. This study used a non-factorial randomized block design (RBD) with a treatment factor of 8 types of organic matter and 3 replications so that there were 27 experimental units. L0 Treatment: Control, L1: Palm oil solid waste, L2: Sugar factory waste, L3: Fish waste, L4: animal feed waste, L5: Chicken manure, L6: Cow manure, L7: Leguminose compost, L8: Compost organic waste fertilizer Medan city with a dose of each organic material 150g / 10 kg TKO. After incubation, bulk density (g /cm3) was taken using the Ring Sample method, Total Pore Space (%) with soil particle density and permeability (cm/hour) using the De Bootd method. Research Results Giving fish waste has the highest significant effect in improving soil physical properties such as reducing soil bulk density, namely 1.02 g / cm3, and increasing the total soil pore space by 61.63%, while the highest soil permeability is obtained in the treatment of animal feed waste, which is 60.22 cm. hour while the lowest was in the Control treatment of 29.11 cm/hour.